2014
DOI: 10.1017/s0029665114000597
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in older subjects: variation, health consequences and dietary intervention prospects

Abstract: Alterations in intestinal microbiota composition and function have been linked to conditions including functional gastrointestinal disorders, obesity and diabetes. The gut microbiome encodes metabolic capability in excess of that encoded by the human genome, and bacterially produced enzymes are important for releasing nutrients from complex dietary ingredients. Previous culture-based studies had indicated that the gut microbiota of older people was different from that of younger adults, but the detailed findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 124 publications
(175 reference statements)
0
17
0
1
Order By: Relevance
“…The interaction between dietary components and intestinal microorganisms shapes the composition of the gut microbiota and thus has a great impact on host metabolism40. The cecum was chosen for sampling because previous studies1241 showed that it is colonized with sufficient quantities of a readily harvested microbiota for metagenomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between dietary components and intestinal microorganisms shapes the composition of the gut microbiota and thus has a great impact on host metabolism40. The cecum was chosen for sampling because previous studies1241 showed that it is colonized with sufficient quantities of a readily harvested microbiota for metagenomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotics may support the Bifidobacterium and Lactobacillus species delivered via probiotic supplementation by providing a fermentable food source for these bacteria, allowing them to flourish. More specifically, it has been reported that prebiotics have the ability to exert a bifidogenic effect on human subjects (O’Connor et al, 2014). …”
Section: The Aging Gutmentioning
confidence: 99%
“…Relevant to IBD, there is evidence that vitamin D deficiency may compromise the gastrointestinal mucosal barrier, whereas active vitamin D appears to promotes epithelial integrity through up-regulation of tight junction proteins zonula occcludens-1 and claudin-1 (61,62) . Some reports suggest changes in the gut microbial composition in animal models (63) in response to vitamin D. Despite immense interest in the gut microbiome (64,65) this has yet to be investigated in response to vitamin D therapy in CD. Although some parallels exist, the degree to which the immune effects observed in animal models translate to human IBD is not fully understood.…”
Section: Vitamin D Status and Associations With Disease Severity In Cmentioning
confidence: 99%